PELATIHAN SOFTWARE MAPLE 18 DALAM MENYELESAIKAN PERMASALAHAN INTEGRAL PADA MATA KULIAH KALKULUS DASAR MAHASISWA INFORMATIKA - Desty Rakhmawati (Yayasan Nusantara Hasana Berdikari, 2023)
Integral is one of the topics discussed in Basic Calculus course which is one of the courses taken by Informatics Students. Based on the problems experienced by students, related to the subject is in the Integral concept. In Basic Calculus lectures which have 2 credits and no practicum, it requires additional theory related to the use of software that can be used in understanding integral concepts. Therefore, this training provides training related to the use of computer technology in the form of Maple 18, which can be used to understand and complete the Integral concept. And after the training, the evaluation results show that the training process provides an understanding related to the use of Maple 18 to solve Integral concept problems. Thus, Informatics students not only understand the concept in theory manually, but also understand the Integral concept with the help of software, namely Maple 18.